Evaluation and optimal selection of Dunhuang radiometric calibration site based on OLI/Landsat 8 and MSI/Sentinel 2 data. Issue 5 (4th March 2022) - Zhu, Sifeng; Li, Zhengqiang; Hu, Xiuqing; Qie, Lili; Xu, Hua; Qiao, Rui; Zhang, Yuhuan; Golry, Philippe
ABSTRACT: The Dunhuang radiometric calibration site is an important component of the China Radiometric Calibration Sites (CRCS), which has served for in-flight radiometric calibration of Chinese satellites sensors since the 1990s, whereby the homogeneity has been verified since its construction. However, due to the increasing demand for radiometric calibration of the in-flight satellite sensors, and the impacts of a changing natural environment and the destruction of human activities of the site, it is essential to reassess the homogeneity of Dunhuang site and redefine the suitable region for calibration. Accordingly, the homogeneity of the Dunhuang site is reevaluated based on the satellite images of OLI/Landsat 8 (with resolutions of 30 m) and MSI/Sentinel 2 (with resolutions of 10 m) observed from 2015 to 2021. An ROI of 50 × 75 km is selected covering three historical definitions of the Dunhuang site with an area of 25 × 25 km, 20 × 20 km, and 10 × 10 km, respectively. Firstly, the spatial-temporal coefficients of variation ( C V S T ) of the ROI is calculated. The homogeneity of the three existing sites is analyzed, and the results show that the 20 km site (40.06° N−40.25° N, 94.25° E−94.42° E) has the best homogeneity among the existing sites in Dunhuang. Then, by using a hierarchical region statistical method, three optimal locations and scopes of the Dunhuang site (10 × 10 km: 40.044° N−40.144° N, 94.284° E−94.384° E; 20 × 20 km: 40.002° N−40. 202° N, 94.216° E−94.416° E; 25 × 25 km: 40.021° N−40.247° N, 94.071° E−94.364° E) are defined. The average C V S T of the three OGT sites decrease from about 0.94%～2% to 0.7%～1.54% relative to the existing sites, and the standard deviation of C V S T decrease from about 0.45%～2% to 0.24%～1%. The Getis statistics also indicate that they are more homogeneous than the existing definitions of the site. Additionally, the optimal Dunhuang sites are compared with the north Africa Pseudo-Invariant Calibration Sites (PICS). The homogeneity of optimal Dunhuang sites is proved to be better than most sites hence that could be the complement for each other. These three optimal Dunhuang sites are new candidate sites served for the satellite in-flight radiometric calibration.